1997
DOI: 10.1097/00001888-199702000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Three medical schoolsʼ responses to the HIV/AIDS epidemic and the effect on studentsʼ knowledge and attitudes

Abstract: Differences in HIV/AIDS prevalences did not affect the schools' training programs, but indirectly affected the students' knowledge and attitudes, which were related to the numbers of HIV-infected individuals known personally by the students. The authors recommend that medical schools increase students' opportunities for meaningful personal contact with HIV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…First and foremost their knowledge on HIV improved, clearing some of the misconceptions they had. Some of the students had an experience of caring for an HIV positive relative which also significantly helped them to change their attitudes and this is consistent with previous research (Anderson et al, 1997;Bektaş & Kulakaç 2007;Peate et al 2002). Cunningham et al (2006) also revealed that previous experience of looking after ill family members or friends influence students' attitudes and approach to care.…”
Section: Synthesis and Discussionsupporting
confidence: 81%
“…First and foremost their knowledge on HIV improved, clearing some of the misconceptions they had. Some of the students had an experience of caring for an HIV positive relative which also significantly helped them to change their attitudes and this is consistent with previous research (Anderson et al, 1997;Bektaş & Kulakaç 2007;Peate et al 2002). Cunningham et al (2006) also revealed that previous experience of looking after ill family members or friends influence students' attitudes and approach to care.…”
Section: Synthesis and Discussionsupporting
confidence: 81%
“…19 Consequently, earlier research has assessed students' knowledge about HIV/AIDS and other infectious diseases. [20][21][22][23][24][25] Increased knowledge, however, has only limited effects on reducing fears associated with treating infectious patients and virtually no effect on the willingness to treat these patients. 19,26 Additionally, while dental students had a high level of knowledge of infection control procedures and were more likely to adhere to these procedures than were medical students, they were significantly less likely than medical students to report a desire to treat patients with infectious diseases such as HIV/AIDS.…”
mentioning
confidence: 99%
“…Changes over a period of time or subsequent to some form of intervention can also be easily quantified. This is identical to the methods adopted by other researchers involved in similar studies [13][14][15][16].…”
Section: Discussionmentioning
confidence: 87%
“…Anderson et al reported differences in medical students' knowledge about HIV due to different curricula in medical schools [14]. Admission into the medical school in the University of Kuopio requires that intending students pass standardized tests designed in line with the University curriculum.…”
Section: Discussionmentioning
confidence: 99%